La inmunidad de jurisdicción frente a las normas jus cogens relacionadas con los Derechos Humanos : un análisis jurisprudencial a la luz de la fragmentación del derecho internacional - Brichetti, Florencia Mariana (2018)
This investigation work has the aim to reflect on jurisdictional immunity of States and International Organizations, as well as their agents. The complexity of the matter motivates a series of especially interesting questions, which can be problematized through the study of the mentioned immunity principles. Our aim is to analyze the evolution of international law regarding this topic to prove that, even though there is not a uniform rule that allows to establish the totality of the situations different to resignation of immunity in which the immunity falls, it is in fact possible to observe a jurisprudential tendency that establishes a principle on which jurisdictional immunity of States and International Organizations falls in presence of affectation of jus cogens law related to human rights.